Hybrid routing protocol with Quality of Service support for Ad Hoc Wireless Networks. (5th February 2008) - Alaoui, Amine; Quintero, Alejandro; Ivascu, Gabriel Ioan
In Mobile Ad Hoc Networks (MANETs), mobile nodes must collaborate amongst themselves to interconnect and establish communication. Moreover, their networking characteristics highlight a new breed of unresolved routing and Quality of Service problems. In this paper we present a hybrid routing protocol with quality of service support. In this protocol, each mobile node keeps in memory not only available routes to destinations but also good routes in term of quality of service. The results obtained from simulations confirm the validity of our approach and show that our protocol clearly outperforms protocols from both the proactive and reactive type.